1. 25/36*x^4+5*x^2+9
2. 1/64*x^2-x^2+16*n^2
3. 4/49*m^2+4*m*n^3+49*n^6
4. 1/36*p^6+n*p^3+9*n^2
5. 9/25*c^3+6*c^3*t^4+25*t^8
6. x^4*y^2-2*x^2*y*k*n^2+k^2*n^4
Объяснение:
Следуя формулам (a+b)^2=a^2+2*a*b+b^2
(a-b)^2=a^2-2*a*b+b^2
1. (5/6x^2+3)^2=(5^2)/(6^2)x^4+2*3*5/6x^2+3^2=25/36 x^4+5x^2+9
2. (1/8x^2-4n)^2=1/64x^4-2*4*1/8 x^2+(4n)^2=1/64*x^2-x^2+16n^2
3. (2/7m+7n^3)^2=4/49 m^2+2*2/7*7 *m*n^3+49n^6= 4/49*m^2+4*m*n^3+49*n^6
4. (1/6 p^3+3n)^2=1/36 p^6+2*1/6*3*p^3*n+9n^2=1/36*p^6+n*p^3+9*n^2
5. (3/5 c^3+5t^4)^2=9/25*c^6+2*5t^4*3/5*c^3+25*t^8= 9/25*c^3+6*c^3*t^4+25*t^8
6. (x^2y-kn^2)^2=x^4*y^2-2*x^2*y*k*n^2+k^2*n^4
1) а) √D = √(49-4*2*(-9)) = √121 = 11
x1,2 = (-b±√D)÷2a = (-7±11)÷4
x1 = (-7+11)÷4 = 1
x2 = (-7-11)÷4 = -4,5
б) 3х² - 18х = 0
3х(х-6) = 0
3х = 0 или х-6 = 0
х1 = 0, х2 = 6
в) 100х² - 16 = 0
100х² = 16
х = √0,16 = ±0,4
х1 = -0,4; х2 = 0,4
г) х² - 16х + 63 = 0
х1 + х2 = -b; x1 × x2 = c
x1 = 9; x2 = 7
2) 2(a+b) = 20; a×b = 24
a+b = 20/2 = 10, a = 10 - b
(10-b)b = 24; b²-10b+24 = 0
b = 6; 4
ответ: 6 см и 4 см
3) х1+х2 = -p; x1 × x2 = c
x1 - 9 = -p; -9*x1 = -18
x1 = -18/-9 = 2; p = -(2 - 9) = 7
ответ: х1 = 2; р = 7
Отметь как лучший